Live attenuated-nonpathogenic Leishmania and DNA structures as promising vaccine platforms against leishmaniasis: innovations can make waves - Seyed, Negar; Taheri, Tahereh; Rafati, Sima (Frontiers in Microbiology, 2024)
Leishmaniasis is a vector-borne disease caused by the protozoan parasite of Leishmania genus and is a complex disease affecting mostly tropical regions of the world. Unfortunately, despite the extensive effort made, there is no vaccine available for human use. Undoubtedly, a comprehensive understanding of the host-vector-parasite interaction is substantial for developing an effective prophylactic vaccine. Recently the role of sandfly saliva on disease progression has been uncovered which can make a substantial contribution in vaccine design. In this review we try to focus on the strategies that most probably meet the prerequisites of vaccine development (based on the current understandings) including live attenuated/non-pathogenic and subunit DNA vaccines.Innovative approaches such as reverse genetics, CRISP/R-Cas9 and antibiotic-free selection are now available to promisingly compensate for intrinsic drawbacks associated with these platforms.Our main goal is to call more attention towards the prerequisites of effective vaccine development while controlling the disease outspread is a substantial need.